Juridical Review Of Mortgage Execution In Bad Credit Cases: A Civil Procedure Law Perspective - Arif, Ahmad (Equality : Jurnal Hukum dan Keadilan, 2025)
This study critically examines the effectiveness of mortgage right execution under Indonesian civil procedural law in addressing non-performing loans. Employing a normative juridical approach through literature review, it analyzes statutory provisions and legal doctrines, particularly Law No. 4 of 1996 on Mortgage Rights. The findings reveal that despite the availability of mechanisms such as parate executie, executorial titles, and private sales, practical implementation remains hindered by complex bureaucracy, debtor objections, and procedural inefficiencies. The study highlights the potential role of digitalization, particularly blockchain technology, in enhancing transparency and legal certainty. It recommends regulatory harmonization, development of digital infrastructure, and a rights-based legal framework to strengthen protection for creditors, debtors, and third parties.